Busting the Breast Cancer with AstraZeneca’s Gefitinib - S. Chemmalar; A. R. Intan Shameha; Che Azurahanim Che Abdullah; Nor Asma Ab Razak; Loqman Mohamad Yusof; Mokrish Ajat; Kim Wei Chan; Md Zuki Abu Bakar Zakaria (Advances in Pharmacological and Pharmaceutical Sciences)
Breast cancer is the most common cancer diagnosed in women, and in 2020, there were 684, 996 deaths due to this disease. Epidermal growth factor receptors (EGFRs) and their respective ligands have been blamed for the pathogenesis and resistance to treatment in specific breast cancer cases. With EGFR having four homologues: EGFR1, EGFR2, EGFR3, and EGFR4, in-depth understanding of EGFR biology led to the discovery of small-molecule inhibitors and antibodies against this receptor. Gefitinib (GEF), a tyrosine kinase inhibitor of EGFR1, possesses a vast potential for treatment against breast cancer and is supported by a multiplicity of experiments. Unfortunately, in clinical trials, GEF did not show the outcomes expected with complete response and disease progress. This is due to incomplete understanding of the molecular mechanisms involved in EGFR signaling and endocrine sensitivity. Hence, additional in-depth experiments are needed regarding various molecular pathways and crosstalk pathways to comprehend GEF’s action mechanism thoroughly in breast cancer patients. In this review, the role of EGFR in the development and pathogenesis of breast cancer and the pharmacokinetics and pharmacotherapy of GEF for the treatment of breast cancer have been elaborated. Nanomedicines synthesized with GEF have shown positive experimental response, paving a promising path for GEF against breast cancer.